Upward-Oriented Complementizer Agreement With Subjects And Objects In Kipsigis - Diercks, Micheal; Rao, Meghana (My University, 2019)
In Kipsigis (Nilotic, Kenya), declarative-embedding complementizers can agree with both main-clause subjects (Subj-CA) and main-clause objects (Obj-CA). Subj-CA agrees with the closest super-ordinate subject (even in the context of intervening objects), cannot agree with non-subjects or embedded subjects, and yields an interpretation where the embedded clause is the main point of the utterance. Obj-CA can only target main-clause objects and can only occur on a complementizer already bearing Subj-CA; Obj-CA contributes a verum focus reading to the clause. The paper briefly considers the analytical implications of these patterns.
Keywords: Kipsigis; objects; complementizer agreement; embedded clause